Sistem Pendukung Keputusan Pemilihan Pegawai Non PNS Kantah Kota Medan Terbaik Menggunakan Metode MOORA - Sri Wulan; Adinda Rezeki Syahputri Samosir (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The Medan City Land Office was established by the Medan City Government which has the main task of carrying out community affairs, so Non Civil Servants (Honorer) are directly handled by government agencies in the Medan City area, so they work with companies which are at the Medan City Land Office which is to help the community.Meanwhile, for temporary employees, the handling starts from recruitment, payment of honorary salaries, with their dismissal being the authority and responsibility of the government (central and regional) where they work. national, regional and sectoral.decision support system (DSS) to overcome these problems, the most appropriate is using the MOORA (Multi-Objective Optimization on The Basis of Ratio Analysis) method used to determine the quality of the honorary employee by looking at the elements that affect a problem with good quality.The results in this study are a decision support system for the assessment of non-civil servants using the MOORA method at the Medan city land office which can take into account all the criteria, there is a result that the best value that has the highest alternative is considered the best, namely Rina Erviana so that the largest optimization value is -206.25